2017
DOI: 10.1038/ijo.2017.130
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal atrophy and altered brain responses to pleasant tastes among obese compared with healthy weight children

Abstract: Objective The hippocampus is a key structure implicated in food motivation and intake. Research has shown that the hippocampus is vulnerable to the consumption of a western diet (i.e., high saturated fat and simple carbohydates). Studies of patients with obesity (OB), compared to healthy weight (HW), show changes in hippocampal volume and response to food cues. Moreover, evidence suggests that OB children, relative to HW, have greater hippocampal response to taste. However, no study has examined the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 57 publications
6
54
1
Order By: Relevance
“…The linear regression models were unadjusted models (Model 1), and models adjusting for ICV (Model 2), ICV and child age (Model 3), and with additional adjustments for SES and exposure to maternal GDM (Model 4), and additionally, child BMI z ‐score (Model 5). These covariates were previously shown to influence hippocampal volume and thus were added to the model to control for potential confounding (Bauer et al, ; Hair, Hanson, Wolfe, & Pollak, ; Jabès, Thomas, Langworthy, Georgieff, & Nelson, ; Krogsrud et al, ; Mestre et al, ; Uematsu et al, ). Since the majority (93%) of children were prepubertal (Tanner stage < 2), Tanner stage was not adjusted in the regression models.…”
Section: Methodsmentioning
confidence: 99%
“…The linear regression models were unadjusted models (Model 1), and models adjusting for ICV (Model 2), ICV and child age (Model 3), and with additional adjustments for SES and exposure to maternal GDM (Model 4), and additionally, child BMI z ‐score (Model 5). These covariates were previously shown to influence hippocampal volume and thus were added to the model to control for potential confounding (Bauer et al, ; Hair, Hanson, Wolfe, & Pollak, ; Jabès, Thomas, Langworthy, Georgieff, & Nelson, ; Krogsrud et al, ; Mestre et al, ; Uematsu et al, ). Since the majority (93%) of children were prepubertal (Tanner stage < 2), Tanner stage was not adjusted in the regression models.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in animals have also found similar results, including impaired neurogenesis (10,11) and increased neurodegeneration (9) in the hippocampus following WD consumption. Previous work with children has found a relationship between obesity and left hippocampal volume (31,32). However, these studies did not investigate diet specifically.…”
Section: Discussionmentioning
confidence: 97%
“…Although this relationship was seen in both hemispheres, it was stronger for the left hippocampus. Furthermore, similar reductions in left hippocampal volume have been found in obese children compared to healthy weight peers [ages 6-8 and 8-12, respectively, (31,32)]. However, as multiple factors can contribute to obesity, the specific impact of diet on hippocampal volume in early development remains unknown.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations